Economic and political determinants of budget deficits in the European Union: a dynamic random coefficient approach - Ali Bayar; Bram Smeets (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper formulates a dynamic Random Coefficient Model (RCM) to consider a set of popular determinants of public deficits in the EU-15 over the period 1971-2006, both at a country-specific level and from a population-wide perspective. Although the extent of government deficits and debt has been one of the most debated macroeconomic issues in recent times, the models trying to capture the explanatory powers driving these deficits typically estimate models that pose the strict assumption of homogeneity on the coefficients over all countries in the model. The sensibility of this assumption will be investigated, with results showing that an increase in the degree of heterogeneity leads to an improvement in the model fit and provides additional information to nuance the effects of the explanatory variables. In this way, the paper exposes a limited degree of partisanship over all countries under consideration, but on the other hand provides evidence for opportunistic behaviour of policymakers in the major part of the sample. The effect of institutional changes following the enforcement of the Maastricht Treaty varies over the countries and is related to the necessity of budgetary consolidation.
Keywords: C11; E6; H6; H87; 330; Fiscal policy; European Monetary Union; Random coefficient model; Bayesian analysis; Finanzpolitik; Haushaltsdefizit; Public Choice; Europäische Wirtschafts- und Währungsunion; Konvergenzkriterien; Zustandsraummodell; Schätzung; EU-Staaten